The first characterization of two type I interferons in turbot (scophthalmus maximus) reveals their differential role, expression pattern and gene induction - Pereiro, Patricia; Costa, M. M.; Díaz-Rosales, Patricia; Dios, S.; Figueras Huerta, Antonio; Novoa, Beatriz (Developmental & Comparative Immunology, 2014)
12 páginas, 1 apéndice, 7 figuras Type I interferons (IFNs) are considered the main cytokines directing the antiviral immune response in vertebrates. These molecules are able to induce the transcription of interferon-stimulated genes (ISGs) which, using different blocking mechanisms, reduce the viral proliferation in the host. In addition, a contradictory role of these IFNs in the protection against bacterial challenges using murine models has been observed, increasing the survival or having a detrimental effect depending on the bacteria species. In teleosts, a variable number of type I IFNs has been described with different expression patterns, protective capabilities or gene induction profiles even for the different IFNs belonging to the same species. In this work, two type I IFNs (ifn1 and ifn2) have been characterized for the first time in turbot (Scophthalmus maximus), showing different properties. Whereas Ifn1 reflected a clear antiviral activity (over-expression of ISGs and protection against viral haemorrhagic septicaemia virus), Ifn2 was not able to induce this response, although both transcripts were up-regulated after viral challenge. On the other hand, turbot IFNs did not show any protective effect against the bacteria Aeromonas salmonicida, although they were induced after bacterial challenge. Both IFNs induced the expression of several immune genes, but the effect of Ifn2 was mainly limited to the site of administration (intramuscular injection). Interestingly, Ifn2 but not Ifn1 induced an increase in the expression level of interleukin-1 beta (il1b). Therefore, the role of Ifn2 could be more related with the immune regulation, being involved mainly in the inflammation process This work has been funded by the project CSD2007-00002 “Aquagenomics” and AGL2011-28921-C03 from the Spanish Ministerio de Ciencia e Innovación. P. Pereiro gratefully acknowledges the Spanish Ministerio de Educación for a FPU fellowship (AP2010-2408) Peer reviewed